Uniting the Vision for Health Equity through Partnerships: The 2nd Annual Dr. Elijah Saunders & Dr. Levi Watkins Memorial Lecture - Pérez-Stable, Eliseo J. (Ethn Dis, 2019)
Minority health research focuses on outcomes by race and ethnicity categories used in the United States census. Overall mortality has decreased significantly for African Americans, Latinos, and Asians over the past 20 years even though it has stopped improving for poor Whites and continues to increase for American Indians/Alaska Natives. Prevention and treatment of cardiovascular disease partly account for this trend, but there is room for improvement. Health disparities research also includes persons of less privileged socioeconomic status, underserved rural residents, and sexual and gender minorities of any race and ethnicity when the outcomes are worse than a reference population. Understanding mechanisms that lead to health disparities from behavioral, biological, environmental and health care perspectives will lead to interventions that reduce these disparities and promote health equity. Experiences with racism and discrimination generate a chronic stress response with measurable effects on biological processes and study is needed to evaluate long-term effects on health outcomes. A clinical example of effective approaches to reducing disparities is management of hypertension to promote stroke reduction that requires health system changes, patient-clinician partnerships and engagement of community organizations. Clinicians in health care settings have the potential to promote health equity by implementing standardized measures of social determinants, leveraging the power of health information technology, maximizing cultural competence and socially precise care and engaging communities to reduce health disparities. Strategic partnerships between health care institutions and community-based organizations need to parallel patient-clinician partnerships and are essential to promote health equity and reduce disparities.